Some results of evaluating the level of sustainable development of agricultural production in Mongolia (Mongolian Journal of Agricultural Sciences, 2019)
In this research work, we evaluated the level of the sustainable agricultural development of Mongolia by a criteria consisting of 3 sub-systems and 14 indicators with a multi-index comprehensive evaluation method by using the data of 2005-2017. According to the research, the sustainable agricultural development level has reached 55.53%, where the economic sub-system has the highest impact and the social sub-system has the lowest impact but the development tendency of the environmental sub-system is at the same level as the general level and the level of sustainable agricultural development strongly depends on the environmental and climatic conditions.